Cutaneous Ulcer as Leading Symptom of Systemic Cytomegalovirus Infection - Richard F. Guo; Frew H. Gebreab; Emily Hsiang-Ho Tang; Zhe Piao; Steve S. Lee; Mario L. Perez (Case Reports in Infectious Diseases)
Cytomegalovirus (CMV) infection rarely manifests with skin ulcerations. We describe a case report of a 64-year-old woman with chronic immunosuppression for treatment of mixed connective tissue disease, presenting with new onset leg ulcerations after a recent change in immunosuppressive regimen. She subsequently developed fulminant hepatitis, encephalopathy, and pancytopenia and was found to have severe systemic CMV viremia. Skin ulcer biopsy was positive by immunohistochemical staining for CMV infected endothelial cells. Both systemic disease and skin ulcer rapidly improved after stopping immunosuppression and administering intravenous ganciclovir. New onset skin ulcers in an immunosuppressed individual, especially with recent changes in immunosuppressive regimen, should raise the suspicion of reactivation of CMV.